IMPLEMENTASI MODEL GAME-BASED LEARNING DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KEAKTIFAN SISWA SD - Muhammad Alfarisi; Andi Widiono; Andriyansah (Universitas Muhammadiyah Metro, 2025)
Abstract: This study aims to implement the Game-Based Learning model in improving student activity and learning outcomes in science learning in grade IV of SD N 1 Sidomulyo. Using the classroom action research (CAR) method with two cycles, this study applies the educational game